Apparatus for connection to public telecommunications systems using the Digital Access Signalling System No. 2 (DASS 2) via a 2048 kbit/s CCITT Recommendation G.703 interface. Requirements for apparatus for connection to Channel Associated Signalling Systems (CASS) Part 3, (15th November 1998) - British Standards Institution,
No abstract available